Radiation of Electric and Magnetic Dipole Antennas in Magnetically Anisotropic Media - Sautbekov, S. S.; Kanymgaziyeva, I. A.; Frangos, P. V. (Elektronika ir Elektrotechnika, 2010)
In this paper the exact analytical solutions of the Maxwell equations in boundless magnetically anisotropic media are obtained in the vector type by the method of generalized functions at the action of the distributed currents. The electrical and magnetic dipole directional diagrams are plotted. Ill. 6, bibl. 4 (in English; summaries in English; Russian and Lithuanian).